Merawat Dunia melalui Kearifan Lokal: Tradisi Grebeg Maulud Yogyakarta dalam Perspektif Islam Nusantara - Abadi, Ali; Fadhilah, Iman; Husna, Akhsanul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores the Grebeg Maulud tradition in Yogyakarta as a manifestation of local wisdom within the framework of Islam Nusantara. Grebeg Maulud is a ceremonial procession conducted annually in the Sultanate of Yogyakarta to commemorate the birth of Prophet Muhammad. The significance of the tradition lies not only in its religious dimension but also in its social, cultural, and environmental aspects that contribute to community cohesion and moral values. Employing a qualitative approach with ethnographic and historical methods, the research examines how Grebeg Maulud embodies local wisdom (kearifan lokal) that encourages harmonious living, mutual cooperation, and respect for nature. The study situates Grebeg Maulud within the worldview of Islam Nusantara, a contextual and inclusive interpretation of Islam grounded in Indonesian cultural realities. Findings suggest that Grebeg Maulud functions as a living tradition that nurtures spiritual piety, social solidarity, and ecological responsibility, thus contributing to the broader agenda of “caring for the world” (merawat dunia) through culturally rooted religious practice.